Akses Petani terhadap Pembiayaan Usahatani Padi di Jawa Barat Dikaitkan dengan Kondisi Agroekosistemnya - Rasmikayati, Elly; Djuwendah, Endah; Saefudin, Bobby Rachmat (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Rice farming is an important agricultural activity in meeting the main food needs of the Indonesian people. Rice farming needs to be supported by adequate sources of financing. However, in practice, many farmers still have difficulty accessing farming financing because the agro-ecosystem conditions do not support each other. The purpose of this study was to identify the relationship between farmers' access to farming financing and their agro-ecosystem support. This study used a quantitative research design using descriptive and inferential statistics. The sample size of the study was 281 rice farmers in West Java from cluster random sampling results. The results showed that the majority of farmers generally consider that all indicators of access to farming financing to be still not supportive. Meanwhile, for the agro-ecosystem, farmers considered that most agro-ecosystem indicators had supported their farming except for OPT attacks which according to most farmers were still difficult to control. Correlation analysis showed that there was a significant relationship between farmers' access to financing and agro-ecosystem support for rice farming in West Java.